Laterally Transferred Gene Recruited as a Venom in Parasitoid Wasps. (29th December 2015) - Martinson, Ellen O.; Martinson, Vincent G.; Edwards, Rachel; Mrinalini,; Werren, John H.
Abstract: Parasitoid wasps use venom to manipulate the immunity and metabolism of their host insects in a variety of ways to provide resources for their offspring. Yet, how genes are recruited and evolve to perform venom functions remain open questions. A recently recognized source of eukaryotic genome innovation is lateral gene transfer (LGT). Glycoside hydrolase family 19 (GH19) chitinases are widespread in bacteria, microsporidia, and plants where they are used in nutrient acquisition or defense, but have previously not been known in metazoans. In this study, a GH19 chitinase LGT is described from the unicellular microsporidia/ Rozella clade into parasitoid wasps of the superfamily Chalcidoidea, where it has become recruited as a venom protein. The GH19 chitinase is present in 15 species of chalcidoid wasps representing four families, and phylogenetic analysis indicates that it was laterally transferred near or before the origin of Chalcidoidea (∼95 Ma). The GH19 chitinase gene is highly expressed in the venom gland of at least seven species, indicating a role in the complex host manipulations performed by parasitoid wasp venom. RNAi knockdown in the model parasitoid Nasonia vitripennis reveals that—following envenomation—the GH19 chitinase induces fly hosts to upregulate genes involved in an immune response to fungi. A second, independent LGT of GH19 chitinase from microsporidia into mosquitoes was also found, also supported by phylogenetic reconstructions. Besides these two LGT events, GH19 chitinase is not found in any other sequenced animal genome, or in any fungi outside the microsporidia/ Rozella clade.